Adherence and intracellular parasitism of Paracoccidioides brasiliensis in Vero cells - Hanna, S. A.; da Silva, JLM; Mendes-Giannini, Maria José Soares [UNESP] (Elsevier B.V., 2000)
Paracoccidioides brasiliensis is a dimorphic fungus known to produce invasive systemic disease in humans. The 43-kDa glycoprotein of P, brasiliensis is the major diagnostic antigen of paracoccidioidomycosis and may act as a virulence factor, since it is a receptor for laminin. Very little is known about early interact-ions between this fungus and the host cells, so we developed in vitro a model system employing cultured mammalian cells (Vero cells), in order to investigate the factors and virulence mechanisms of P. brasiliensis related to the adhesion and invasion process. We found that there is a permanent interaction after 30 min of contact between the fungus and the cells. The yeasts multiply in the cells for between 5 and 24 h. Different strains of P, brasiliensis were compared, and strain 18 thigh virulence) was the most strongly adherent, followed by strain 113 (virulent), 265 (considered of low virulence) and 113M(mutant obtained by ultraviolet radiation, deficient in gp43). P. brasiliensis adhered to the epithelial cells by a narrow tube, while depressions were noticed in the cell surface, suggesting an active cavitation process. An inhibition assay was performed and it was verified that anti-gp43 serum and a pool of sera from individuals with paracoccidioidomycosis were able to inhibit the adhesion of P. brasiliensis to the Vero cells. Glycoprotein 43 (gp43) antiserum abolished 85 % of the binding activity of P. brasiliensis. This fungus can also invade the Vero cells, and intraepithelial parasitism could be an escape mechanism in paracoccidioidomycosis. (C) 2000 Editions scientifiques et medicales Elsevier SAS.
Keywords: Paracoccidioides brasiliensis; adhesion; invasion